Revision of the Palaearctic species and review of the Oriental species of Ooctonus (Hymenoptera: Mymaridae), with notes on extralimital taxa - Triapitsyn, Serguei V. (Zootaxa, 2010)
The fairyfly genus Ooctonus Haliday (Hymenoptera: Mymaridae) from the Palaearctic region is revised. Twelve speces are recognized, including the newly described O. lokomotiv Triapitsyn sp. n. (Far East of Russia), O. saturn Triapitsyn sp. n. (Far East of Russia, and Japan), O. spartak Triapitsyn sp. n. (Kyrgyzstan), O. tretiakovi Triapitsyn sp. n. (Far East of Russia), and O. us Triapitsyn sp. n. (Japan, and Republic of Korea). All the species are redescribed, illustrated, and diagnosed, as is the Oriental species O. himalayus Subba Rao, based mainly on non-type specimens from Nepal (its male is newly described). Taxonomic notes are provided on the other three previously described Oriental species of Ooctonus and one new Oriental species, O. lapen Triapitsyn sp. n., is described from Nepal. Extralimital records are included for the species with Holarctic distribution. Twenty-five new synonymies are proposed: O. major Foerster syn. n., O. elegantissimus Soyka syn. n., O. austriacus Soyka syn. n., O. silvestris Soyka syn. n., and O. isotomus Mathot syn. n. under O. insignis Haliday; O. acutiventris Soyka syn. n., O. askhamensis Hincks syn. n., O. collinus Soyka syn. n., O. stammeri Soyka syn. n., O. viennensis Soyka syn. n., O. niger Soyka syn. n., and O. americanus Girault syn. n. under O. vulgatus Haliday; O. amoenus (Foerster) syn. n., O. hemipterus igneus Debauche syn. n., O. foersteri Soyka syn. n., O. wagneri Soyka syn. n., and O. pechlaneri Soyka syn. n. under O. hemipterus Haliday; O. atroflavus Soyka syn. n., O. diversicornis Soyka syn. n., and O. auripes Whittaker syn. n. under O. notatus Walker; O. polonicus Soyka syn. n., O. montanus Soyka syn. n., O. remonti Mathot syn. n., and O. dovrensis Solem & Sveum syn. n. under O. sublaevis Foerster; and O. flaviventris Donev syn. n. under O. novickyi Soyka. Ooctonus sevae Risbec (from Madagascar) is transferred to Gonatocerus Nees ab Esenbeck as Gonotocerus (Lymaenon) sevae (Risbec), comb. n. Lectotypes are designated for O. austriacus Soyka, O. elegantissimus Soyka, O. foersteri Soyka, O. heterotomus Foerster, O. major Foerster, and O. sub-4 · Zootaxa 2381 © 2010 Magnolia Presslaevis Foerster. Separate keys are provided to females of Ooctonus from the Palaearctic region, to both sexes of the European species, and also to females of the known Oriental species of Ooctonus. A brief diagnosis of the genus is given based on its world fauna, and information on the distribution and known host associations of Ooctonus species is provided. A historical account of the Walter Soyka collection of microhymenoptera is presented, with references to the Arnold Foerster collection of Mymaridae.